Tri‐level decision‐making framework for strategic trading of demand response aggregator. Issue 12 (3rd July 2019) - Jia, Yulong; Mi, Zengqiang; Yu, Yang; Song, Zhuoliang; Fan, Hui
Abstract : This article presents a new decision‐making framework for strategic trading of demand response aggregator (DRA). The proposed framework consists of three layers. At the first layer, the wholesale energy market operated by independent system operator (ISO), which seeks to maximise the social welfare in day‐ahead (DA) market and to minimise the cost of minimise the cost for maintaining energy balance in real‐time (RT) markets. At the second layer, the DRA act as an intermediate operator between ISO and flexible customers. Profit‐maximising DRA affects the clearing results of market prices by strategic trading in DA energy market, providing reserve capacity in DA reserve market and offsetting energy deviation in RT. At the third layer, customers seek to optimise the trading strategy between earnings incentive reward from the DRA and considering uncomfortable cost of customers. The tri‐layer framework is modelled as two bilevel optimisation models, which capture interaction between different entities. The bilevel model can be transformed to single level linear model through Karush‐Kuhn‐Tucker conditions and dual theory to solve the couple non‐linear problem. The numerical studies using the IEEE 9‐bus and 118‐bus test systems are presented to illustrate the application of the proposed tri‐layer decision‐making framework.